Comparação da variabilidade da frequência cardíaca entre os sexos: impacto do sedentarismo - Silva, Reberth Magalhães da (2019)
Physical inactivity has been raised as a considerable an important and modifiable factor for the genesis of cardiovascular disease, regardless sex. However, still no clear whether there are differences in the cardiac autonomic modulation between healthy men and women with different levels physical activity. Therefore, our objective was to investigate the differences between sexes, as well as the effects of activity lifestyle, on heart rate variability (HRV) in heathy men and women. A cross-sectional study was conducted with young healthy adults (18-30 years old) distributed into four groups: physically active (n=37) or sedentary men (n=44); and physically active (n=31) or sedentary women (n=40). We evaluated the hemodynamic parameters and body composition. HRV was investigated using spectral analysis. Our results showed lower levels of systolic arterial pressure and cardiac sympatovagal balance (LF/HF) in women. We observed an increase of the 41% in the total variance (VAR-RR) and 34% in the RMSSD (a parasympathetic index) in active vs. sedentary men. Physically active women showed an increase of 74% and 78% in the VAR-RR and RMSSD in relation to sedentary ones. We observed a decrease of 75% and 50% in LF/HF in physically active men and women as compared to sedentary pars. Furthermore, physically active men presented 66% higher levels of LF/HF and 20% lower RMSSD when compared to physically active women. Our results suggest that cardiovascular and autonomic responses were influenced by lifestyle and sex. Physical active lifestyle was able to promote an improvement on HRV, regardless sex. However, physically active women demonstrated better sympathovagal balance than men, suggesting greater cardiovascular protection.